2015
DOI: 10.1111/jan.12762
|View full text |Cite
|
Sign up to set email alerts
|

Dementia caregiver burden association with community participation aspect of social capital

Abstract: Understanding the relation between caregiver burden and social capital will enhance nurses' capacity to explore the concept, the meaning and the politics of social capital to the benefit of dementia caregivers in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 84 publications
0
29
0
Order By: Relevance
“…Seven studies reported evidence of the association between social support and carer outcomes . Social support was examined from a number of different perspectives.…”
Section: Context Of Caringmentioning
confidence: 99%
“…Seven studies reported evidence of the association between social support and carer outcomes . Social support was examined from a number of different perspectives.…”
Section: Context Of Caringmentioning
confidence: 99%
“…Social stress is one of the factors affecting the burden on the family caregiver [10,12]. Therefore, helping families to address their need for 'social capital' (contact that gives access to social, emotional, and practical support) has a positive impact on the caregiver burden [49]. To meet these needs, DCCs should be open during holidays and weekends, and opening hours should be longer and more flexible.…”
Section: Limited Opening Hours -Consequences For the Caregiver's Socimentioning
confidence: 99%
“…1 Family carers play a crucial role in supporting the well-being of people with dementia and their ability to remain living at home. Caring for someone with dementia can increase the carer's risk of social isolation 3 and can cause carers to give up their holidays and hobbies and spend less time with their family and friends. Caring for someone with dementia can increase the carer's risk of social isolation 3 and can cause carers to give up their holidays and hobbies and spend less time with their family and friends.…”
Section: Introductionmentioning
confidence: 99%